2022
DOI: 10.2217/fon-2021-1248
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety Profile of COVID-19 Vaccine in Cancer Patients: A Prospective, Multicenter Cohort Study

Abstract: Aim: To compare the seropositivity rate of cancer patients with non-cancer controls after inactive SARS-CoV-2 vaccination (CoronaVac) and evaluate the factors affecting seropositivity. Method: Spike IgG antibodies against SARS-CoV-2 were measured in blood samples of 776 cancer patients and 715 non-cancer volunteers. An IgG level ≥50 AU/ml is accepted as seropositive. Results: The seropositivity rate was 85.2% in the patient group and 97.5% in the control group. The seropositivity rate and antibody levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 24 publications
3
25
1
Order By: Relevance
“…We found that COVID-19 vaccines effectively prevent COVID-19 infection in patients with metastatic genitourinary cancers. Our findings are comparable to published data in cancer patients, albeit lower than in healthy volunteers [ 13 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that COVID-19 vaccines effectively prevent COVID-19 infection in patients with metastatic genitourinary cancers. Our findings are comparable to published data in cancer patients, albeit lower than in healthy volunteers [ 13 ].…”
Section: Discussionsupporting
confidence: 91%
“…Ariamanesh et al reported a higher seroconversion in younger patients with cancer than 60 years (90.9%, 90%, and 79% in patients <40 years, 40–60 years, and >60 years; respectively, p = .042) [ 19 ]. Multiple studies suggest that patients with solid malignancies are likely to have a higher seroconversion than patients with hematologic malignancies 13 , 19 , 20 , 21 . Joudi et al reported an excellent immune response (93.3%) to vaccination with minimal side effects (local pain and fever in 22.3% and 24.3% of patients, respectively) in their cohort of 160 patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In a study including 346 patients with cancer, the rate of IgG S antibody development after two doses of inactivated SARS-CoV-2 vaccine was 84.1% in patients aged under 60 years; this rate was found to be significantly lower in patients aged over 60 years at 59.3% [ 15 ]. Similarly, in the study of Yasin et al, it was observed that the seropositivity rates were lower after the CoronaVac vaccine in patients with cancer aged over 60 years [ 16 ]. In a study evaluating the development of seropositivity in 102 patients with solid tumors receiving active cancer treatment after two doses of BNT162b2 vaccination seven of 10 patients who remained seronegative were found to be aged 60 years or older; however, pre-vaccination antibody levels were not measured in this study [ 17 ].…”
Section: Discussionmentioning
confidence: 91%
“…In the clinical trial conducted by our group, we evaluated the Spike immunoglobulin G antibodies against SARS‐CoV‐2 levels after CoronaVac, and we found that the seropositivity rate was lower in the cancer patient group than in the control group. 12 But the correlation between antibody response to vaccination and Covid‐19 occurrence is not clear, and measurement of immunoglobulin levels after full‐dose vaccination is not a routine attitude in daily practice. Thus, the only way to evaluate the efficacy of vaccination against SARS‐CoV‐2 is to observe patients for Covid‐19 occurrence after receiving vaccines.…”
Section: Discussionmentioning
confidence: 99%